Assessing the Sympatholytic Effects of SGLT2 Inhibitors in Anuric Haemodialysis Patients Using Microneurography: Study Protocol for a Mechanistic Proof-of-Concept Trial - Aaron Yee Shuen See; Evgenija Blazeska; Awf Abdulrahman Shaban; Mark Thomas; Sayeh Heidari Nejad; Antonella Soarez Dornelles; Anu Joyson; Sally Burrows; Markus Schlaich; Srivathsan Thiruvengadam (Karger Publishers, 2024)
Introduction: Sodium-glucose co-transporter 2 inhibitors (SGLT2is) have been shown to provide effective cardiorenal protection, reducing mortality in conditions such as heart failure and chronic kidney disease. While several mechanisms have been identified, recent research has shed light on the drug's ability to attenuate sympathetic nervous system (SNS) activity. Controversy exists on whether this is due to the extra-renal effects of the drug, or simply due to its renoprotective effects. However, recent trials have highlighted the persistent efficacy of SGLT2i despite declining renal function. Therefore, investigating the ability of SGLT2i to attenuate the SNS independently of the kidney could lead to more insight into its mechanism of action. So far, there has been limited research done on investigating the extra-renal effects of SGLT2i in human subjects on dialysis where the glycosuric renal effects of SGLT2i are negligible. This current study therefore aims to investigate the effects of SGLT2i on the SNS in anuric haemodialysis patients. Methods: We developed a protocol for a mechanistic study to investigate the extra-renal effects of SGLT2i on the SNS. The study will be an investigator-led, open-label, prospective study involving 20 adult (aged ≥18 years) haemodialysis patients with a residual urine output of ≤250 mL/day. Participants will be administered empagliflozin 25 mg/day for 6 weeks. Baseline SNS activity will be measured before and after administration by microneurography to assess central SNS outflow. Secondary outcomes such as changes from baseline in SNS stressor response, heart rate variability, and endothelial function will also be examined. We hypothesize that the use of empagliflozin will result in reduced sympathetic drive in anuric haemodialysis patients. Discussion: This will be the first study evaluating the effects of SGLT2i on the SNS in haemodialysis subjects. This study aims to enhance our understanding of the potential role of SGLT2i-induced SNS reduction in the setting of markedly reduced renal function. The study has received ethics approval from the Royal Perth Hospital Human Research Ethics Committee (RGS0000003840) (Australian New Zealand Clinical Trials Registry [ANZCTR] ID: ACTRN12623001237673).